Morphological and ISSR molecular markers reveal genetic diversity of wild hawthorns (Crataegus songorica K. Koch.) in Xinjiang, China - Fang SHENG; Shu-ying CHEN; Jia TIAN; Peng LI; Xue QIN; Lei WANG; Shu-ping LUO; Jiang LI (Journal of Integrative Agriculture, 2017)
The wild hawthorn species, Crataegus songorica K. Koch., is an important wild germplasm resource in Xinjiang, China that has been endangered in recent years. The genetic diversity of C. songorica K. Koch. germplasm in five populations from Daxigou, Xinjiang, China were evaluated based on phenotypic traits and ISSR molecular markers to provide basic information on resource protection, rational utilization and genetic improvement. The F-value for the phenotypic differentiation coefficient of the 33 traits measured ranged from 0.266 to 15.128, and mean value was 13.85%. The variation among populations was found to be lower than that within population. A total of 303 loci were detected within the five populations by 12 primers. Within 298 polymorphic loci, the polymorphism was 98.35%, showing a high genetic diversity in C. songorica K. Koch. The gene diversity within population, total population genetic diversity, genetic differentiation coefficient and gene flow were 0.2779, 0.3235, 0.1408, and 3.0511, respectively. Our results showed that C. songorica K. Koch. from Xinjiang has a high level of genetic diversity at both the phenotypic and molecular levels. Significant genetic differentiation existed within population and the differentiation trend showed a regional association. And in this study, in situ and ex situ conservation approaches were raised for wild hawthorn protection utilization.